Beragama Di Tengah Badai Kemanusiaan - Mutiullah Mutiullah (UIN Sunan Kalijaga Yogyakarta, 2018)
Religion is one requirement of human life. Since beginning of life, human needs religion as guide to appoint the good conditions. It has many contributions to civilizations such as hopefully to save. Also, it gives solving to many human’s problems. Recently, religion has challenging that is to solve many social conflicts as poverty and fundamentalism thoughts. So, what should religion does? There are two answers. The first, religion has to reinterpret his dogma. The second is religion as future ideology must to solve many human problems.